PENGIMPLEMENTASIAN MEDIA PEMBELAJARAN BERBASIS QUIZZIZ DALAM UPAYA PENINGKATAN HASIL BELAJAR SISWA - Ayunda Fanny, Cintya Devi; Mardiani Zain, Ita; Jabir (FKIP Unswagati, 2024)
This study discusses the use of Quizizz-based learning media in an effort to improve the learning outcomes of students in class VII-I of SMPN 28 Surabaya in the Social Sciences subject. The research was conducted over 2 cycles, which included planning, implementation, observation, and reflection in each cycle. These stages were repeated with improvements based on reflections from the previous cycle. Data were collected through pre-tests and post-tests to measure the improvement in student learning outcomes, as well as through the observation of teacher and student activities by observers. This research utilized the Classroom Action Research (CAR) model with a time span of 3 months. The results of this study showed a very significant improvement in student learning outcomes, with a 79% increase in cycle I and an 87% increase in cycle II. Additionally, there was an increase in both teacher and student activities in each cycle. This indicates that Quizizz-based learning media is beneficial in improving student learning outcomes. Keywords: quizziz, media pembelajaran, hasil belajar.